Effect of Arbuscular Mycorrhizae on the Growth and Health of Eucalyptus Pellita Seedlings - Arifin, Zainal; Siregar, Bayo A.; Rosanti, Nidya; Hobo, Kristin B.R.; Rizka Tanna, Halimah Halimah; Amin, Nur; Marolop, Rianto; Indrayadi, Heru; Dewi, Anita; Gafur, Abdul; Tjahjono, Budi (KnE Life Sciences, 2022)
Nursery productivity is an important factor in plantation forest sustainability. Seedling quality contributes significantly to plantation health. Fertilization regimes and pest and disease control are critical. However, environmental concerns have arisen as a result of the use of chemical fertilizers and pesticides. The ideal is to manage nurseries in an environmentally friendly manner while maintaining productivity. The utilization of plant growth-promoting microbes (PGPM) is seen as one option in this effort. It has been demonstrated elsewhere that arbuscular mycorrhizae (AM) can improve the growth and health of host plants. In this study, the effect of two AM products on the growth and health of Eucalyptus pellita seedlings in reduced fertilizer regimes was investigated. The results showed that the AM products were unable to compensate for reduced fertilizer regimes (both to 50% and 25%), in terms of seedling height and diameter, in E. pellita. Further research is needed to determine whether using AM products can reduce the need for fertilizers and/or pesticides. Keywords: Biomass, forest sustainability, nursery, plant growth promoting microbes